Inventory of shared water resources in Western Asia - United Nations. Economic and Social Commission for Western Asia; Bundesanstalt für Geowissenschaften und Rohstoffe (Beirut, Lebanon : United Nations Economic and Social Commission for Western Asia, 2013)
The Inventory of Shared Water Resources in Western Asia is the first UN-led effort to comprehensively assess the state of transboundary surface and groundwater resources in the Middle East. The United Nations Economic and Social Commission for Western Asia (ESCWA) and the German Federal Institute for Geosciences and Natural Resources (BGR) developed the Inventory as a desk study, while working in close consultation with ESCWA member countries, as well as regional and international experts.
part 1. Surface water -- part 2. Groundwater.
Cover title.
Includes bibliographical references.
System requirements for accompanying CD-ROM: Computer with CD-ROM drive.
Keywords: Water-supply -- Middle East; Groundwater -- Middle East